Comparison of Interests in Using Online Dictionaries and Printed Dictionaries in Chinese Learning - Apriyanti Apriyanti; Lily Thamrin; Suhardi Suhardi (Jurnal Mantik, 2022)
Dictionary is a reference book that contains a bunch of vocabularies in a certain order by explaining to the people they refer to and checking. Dictionary are divided by print dictionaries and online dictionaries. Author realizes students that learn Chinese Language not only use printed dictionaries, but also use online dictionaries as learning tools. Author wants to understand students interest in online and printed dictionaries, and also wants to figure out the comparison analysis of students interest in using online and printed dictionaries. In order to achieve this intention, the method used by the author are literature and questionnaire method. Survey targets are class A and class B students from generation 2019, with a total of 33 students. Author analyzed using SPSS application and descriptive research methods. Author figure out that students interest in online dictionaries was higher than printed dictionaries. The total percentage for online dictionaries is 80.61%, then the total percentage for print dictionaries is 63.54%. This proves that the interest in using online dictionaries is higher compared to print dictionaries.